WARU LEAF (Hibiscus tiliaceus) AS SAPONIN SOURCE ON In vitro RUMINAL FERMENTATION CHARACTERISTIC - Istiqomah, L.; Hardian, H.; Febrisantosa, A.; Putra, D. (Diponegoro University, 2011)
The effect of waru leaf (Hibiscus tiliaceus) supplementation as saponin source on ruminalfermentation characteristics were studied using in vitro gas production techniques. Rumen fluid wastaken from fistulated Ongole crossbreed cattle. The treatments consisted of control treatments (Napiergrass with monensin and Napier grass without waru leaf (0% saponin level) and waru leafsupplementation treatments as much as 11, 22, 33, and 44 mg of feed (in dry matter basis) or equal to 5,10, 15, and 20% saponin level added to feed substrate of Napier grass (Pennisetum purpureum). Theresult showed that protozoa numbers and total gas production were significantly reduced (P<0.05) inline with the increasing of saponin level compared to 0% saponin level, while NH3, VFA concentrationand pH after 48 h fermentation were not affected by the treatment. VFA concentration increased by waruleaf up to 10% saponin level then decreased at level 15 and 20%. Ratio of acetate to propionate (A/P)and non glucogenic ratio (NGR) decreased at 5, 10, and 15% saponin level, but increased at level 20%.It could be concluded that waru leaf supplementation at 10% saponin level of feed was the optimumlevel which gave positive effect on rumen feed fermentation.